Antianginal effects of hydroxyfasudil, a Rho-kinase inhibitor, in a canine model of effort angina - Utsunomiya, T (2001)
1. The effects of Rho-kinase inhibitor, fasudil, and of a more specific Rho-kinase inhibitor, hydroxyfasudil, on pacing-induced myocardial ischaemia were determined in anaesthetized open-chest dogs. 2. The dogs were subjected to left anterior descending coronary artery (LAD) stenosis producing a sufficient ischaemia as measured by ST-segment depression on electrocardiograms only when the hearts were paced 60 beats min(−1) above the baseline. After a recovery (nonpacing) period, drugs or saline were infused intravenously over 30 min. The animals were again subjected to 5 min of pacing 25 min after the initiation of the treatment. Hydroxyfasudil (0.1 and 0.3 mg kg(−1)) and fasudil (0.3 mg kg(−1)) suppressed the ST-segment depression. 3. Hydroxyfasudil and fasudil also increased the regional blood flow of the LAD perfused endomyocardium region in the canine model of effort angina. 4. To determine the flow profile for hydroxyfasudil in dogs, blood flow in three vascular beds was measured. Hydroxyfasudil (0.3 mg kg(−1) for 30 min) significantly increased coronary blood flow and vertebral blood flow, without significantly changing the femoral blood flow. 5. Hydroxyfasudil had no inotropic or chronotropic effect on the isolated hearts of guinea-pigs. Hydroxyfasudil (2 mg kg(−1) for 20 min) did not affect the PR or QTc interval in anaesthetized dogs. 6. Inhibition of Rho-kinase appears to protect myocardium subjected to pacing-induced ischaemia through the increase in the regional myocardial blood flow. Hydroxyfasudil may be categorized as a novel type of anti-anginal drug, without any inotropic or chronotropic effects.